Dempster Shafer Theory - yadav, Vishal; Kaushik, Atul; Verma, Rajat (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
The theory of belief functions, also referred to as evidence theory or Dempster–Shafer theory (DST), is a general framework for reasoning with uncertainty, with understood connections to other frameworks such as probability, possibility and imprecise probability theories. In this paper we give a detailed view of the theory